CT-myelography for high-dose irradiation of spinal and paraspinal tumors with helical tomotherapy: revival of an old tool - Uhl, Matthias; Sterzing, Florian; Habl, Gregor; Schubert, Kai; Sroka-Pérez, Gabriele; Debus, Jürgen; Herfarth, Klaus (Strahlentherapie und Onkologie, 2011)
High-dose irradiation or reirradiation of spinal and paraspinal tumors is a challenge particularly in the presence of metal artifacts after surgery. Image-guided advanced intensity-modulated radiotherapy delivers high-dose radiation to the tumor sparing the spinal cord. Precise delineation of the spinal cord is necessary treating para- and intraspinal tumors with a sufficient dose.